2013
DOI: 10.1590/0004-282x20130172
|View full text |Cite
|
Sign up to set email alerts
|

Right cerebral hemisphere and central auditory processing in children with developmental dyslexia

Abstract: Objective We hypothesized that if the right hemisphere auditory processing abilities can be altered in children with developmental dyslexia (DD), we can detect dysfunction using specific tests. Method We performed an analytical comparative cross-sectional study. We studied 20 right-handed children with DD and 20 healthy right-handed control subjects (CS). Children in both groups were age, gender, and school-grade matched. Focusing on the right hemisphere’s contribution, we utilized tests to measure alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
(19 reference statements)
0
7
0
2
Order By: Relevance
“…Alteration for sound localization found at -45 o may results from right Parietal lobe dysfunction, as suggested from data from other researchers 23,24 . Difficulties for localization were also found in positive angles which suggests a link with a left-hemisphere temporo-parietal alteration 25,26 .…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Alteration for sound localization found at -45 o may results from right Parietal lobe dysfunction, as suggested from data from other researchers 23,24 . Difficulties for localization were also found in positive angles which suggests a link with a left-hemisphere temporo-parietal alteration 25,26 .…”
Section: Discussionmentioning
confidence: 52%
“…This was one of the most significant finding of our research, to show the increased difficulties of children with DD, when they have to face a task, that challenge a higher order perceptual network, with a predominance of participation of the neurons decoding stimuli in right cerebral hemisphere. In one study carried-out by Murphy-Ruiz et al, authors observed that although all psychoacoustics tests engaged both cerebral hemispheres, some abnormal tests were linked to right hemisphere processing 24 . Ligges et al observed by means of fMRI and electroencephalography that children with DD used the right-hemisphere analogues areas to the posterior left-hemisphere language areas, to compensate the processing deficits 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In other words, these studies were carried out with children regularly enrolled in educational institutions (19)(20)(21)23,24) , or with children suspected of central auditory processing disorder (22) . The other studies compared 2 (26)(27)(28)(29)(30)(31)(32)34,(36)(37)(38)(39)(40)(41)(42)(43)45,49,51,(54)(55)(56)(57)(58)61) , 3 (25,33,44,(46)(47)(48)50,52,53,59,60) or 5 (62) study groups. It was also found that in 4 studies (26,35,62,63) auditory training was carried out in groups with alterations: participants with reading difficulties (26) and with learning disorders (35...…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the design of studies, it was observed that most of them presented cross-sectional designs (10,19,20,22,24,25,(27)(28)(29)(30)(31)(32)(33)(34)37,38,49), followed by studies with case-control designs (39,(43)(44)(45)50,51,(53)(54)(55)(56)(58)(59)(60)(61) .…”
Section: Resultsmentioning
confidence: 99%
“…Loo JHY, Bamiou DE, Campbell N et al (21) The study of Murphy-Ruiz, Penaloza-López et. al 12 showed that children with developmental dyslexia presented lower performance than children with typical development in all auditory processing tests. Such evidence corroborates the literature, as children with language disorders present alterations in the phonological processing related to an auditory processing disorder, in other words, children with dyslexia present changes in auditory skills 29 .…”
Section: To 7 Yearsmentioning
confidence: 99%